2005
DOI: 10.1002/adfm.200305027
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Electronic Character of Single-Walled Carbon Nanotubes Through Anisotropic Polymer Interaction: A Raman Study

Abstract: Using Raman spectroscopy, we demonstrate that the anisotropic interaction between single‐walled carbon nanotubes (SWNTs) and poly(methyl methacrylate) (PMMA) causes significant changes in the electronic properties of their composites. Two different procedures were used to prepare the composites: melt blending and in‐situ UV polymerization. Resonant Raman studies relate the electronic density of states (DOS) of the SWNTs to the corresponding vibration symmetry changes of both the PMMA and the SWNTs. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…This indicates that the number of sp 3 ‐bonded carbons increased may due to the bond formation between PI and GO during in situ polymerization. The observed results are consistent with the earlier carbon based reports .…”
Section: Resultssupporting
confidence: 93%
“…This indicates that the number of sp 3 ‐bonded carbons increased may due to the bond formation between PI and GO during in situ polymerization. The observed results are consistent with the earlier carbon based reports .…”
Section: Resultssupporting
confidence: 93%
“…Moreover, it was observed that the peak related to the D-band broadened with the increase of the graphene flakes incorporated into the PGS solution before cross-linking, which suggests the formation of covalent bonds between the PGS polymer chains and the graphene flakes. Chen et al [28] observed that the D-band peak of carbon nanotubes broadened during in-situ polymerization of poly(methyl methacrylate) (PMMA), and attributed this phenomenon to covalent bonding between the PMMA chains and the CNT's. Differential scanning calorimetry (DSC) performed on the pristine and nanocomposite PGS samples showed that the polymer had a glass transition around -10 °C, followed by a melting transition with maxima at ~8 °C (figure 4b).…”
Section: Nanocomposite Chemical and Thermal Propertiesmentioning
confidence: 99%
“…Nanocomposites from MWNTs1, 2 with polymers have been reported to improve mechanical strength, electrical and thermal conductivity and thermal stability. A number of papers appeared which deal with processing and characterization of nano‐composites based on CNTs in different polymer matrices, such as epoxy,3–5 nylon,6–9 polycarbonate (PC),10–12 poly(methyl methacrylate) (PMMA)13–15 and polystyrene (PS) 16–19…”
Section: Introductionmentioning
confidence: 99%